Incentive Decision on Safety Investment of Supply Chain of Agricultural Products in “Agricultural Super-Docking” - Weiqin Tang; Weimin Tang; Changsheng Jiang; Shan Lu (Journal of Applied Mathematics)
Since the “agriculture super-docking” mode was introduced in China in 2007, remarkable success has been made in reducing the transaction cost and improving the quality safety of agricultural products. However, the quality safety issues of agricultural products still occur frequently because both specialized farmers’ cooperatives and supermarkets have insufficient safety investment. In order to study the necessity, goal, and incentive decision schemes of safety investment in “agriculture super-docking” supply chain, three kinds of models, which include noncooperatives distributed decision-making model, centralized decision-making model, and incentive coordination models led by cooperatives and supermarkets, are, respectively, set up in this paper. Conclusions are drawn as follows: when making the uncooperative decentralized decision, both cooperatives and supermarkets have the moral risks to decrease the safety investment, but appropriate measures can achieve the coordination of the supply chain; when achieving the coordination of supply chain, the two contacts under the guidance of cooperatives and supermarkets are the same, and the schemes of distributing profits are also the same. Moreover, a practical case is given to improve the effectiveness and feasibility of the incentive decision schemes.